Competitive Binding of Ozanimod and Other Sphingosine 1-Phosphate Receptor Modulators at Receptor Subtypes 1 and 5 - Selkirk, Julie V.; Bortolato, Andrea; Yan, Yingzhuo Grace; Ching, Nathan; Hargreaves, Richard (Frontiers in Pharmacology, 2022)
Ozanimod, a sphingosine 1-phosphate (S1P) receptor modulator, binds with high affinity selectively to S1P receptor subtypes 1 (S1P1) and 5 (S1P5), and is approved in multiple countries for the treating adults with relapsing forms of multiple sclerosis (MS) or moderately to severely active ulcerative colitis (UC). Other S1P receptor modulators have been approved for the treatment of MS or are in clinical development for MS or UC, but it is unknown whether these compounds bind competitively with each other to S1P1 or S1P5. We developed a competitive radioligand binding assay using tritiated ozanimod and demonstrate full displacement of ozanimod by S1P (endogenous ligand), suggesting that ozanimod binds to the S1P1 and S1P5 orthosteric binding sites. S1P receptor modulators FTY720-p, siponimod, etrasimod, ponesimod, KRP-203-p, and amiselimod-p also completely displacing radiolabeled ozanimod; thus, on a macroscopic level, all bind to the same site. Molecular docking studies support these results and predict the binding of each molecule to the orthosteric site of the receptors, creating similar interactions within S1P and S1P5. The absolute free energy perturbation method further validated key proposed binding modes. Functional potency tightly aligned with binding affinities across S1P1 and S1P5 and all compounds elicited S1P1-mediated -arrestin recruitment. Hence, the S1P modulators appear to display similar receptor pharmacology and, accounting for the overall efficacy and safety profile, health care providers can consider that the included S1P receptor modulators bind competitively with one another and thus patients could be offered a switch in medication without the potential for additive pharmacology.